Partisipasi Masyarakat Lokal Dalam Pelestarian Istano Basa Pagaruyung Kabupaten Tanah Datar Sumatera Barat Sebagai Daya Tarik Wisata - Khalida Prima Zola; I Made Adikampana (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2018)
The purpose of this study was to determine local community participation to preservation of Istano Basa Pagaruyung as tourism attraction. Data collection procedures using observation and interviews. Data were analyzed using qualitative descriptive technique. The results based on the description of local community participation in supporting the preservation of Istano Basa Pagaruyung, Tanah Datar regency, West Sumatera as tourist attraction. The types of local community participation to support preservation of Istano Basa Pagaruyung is participation in implementation and participation in taking of benefits. While on the type of participation in decision making and evaluation, the local community does not have an active role. Local communities participate as man power, treasure an skills. While there is no participation of idea or thought that have done by local resident around Istano Basa Pagaruyung tourist attraction. Keywords: Participation, community, concervation